New harmonic mitigation scheme for modular multilevel converter – an experimental approach. Issue 12 (1st December 2014) - Sreedhar, Madichetty; Dasgupta, Abhijit; Mishra, Sambeet
Abstract : The multilevel converter has been brought into limelight in this study; however, particular attention has been provided to the form and function of modular multilevel converter (MMC) with new controller to mitigate the circulating currents and harmonics present in the system. Till date, research in this field is very limited with circulating currents and harmonics as the major problem. The stability analysis of proposed controller has been derived and analysed with its experimental results. The system is examined before and after application of controller and results is analysed. This article effectively addresses the problem with prototype of 1 KVA implementation and attempts to make a detailed analysis with their functions in comprehensive manner with HVDC application under different conditions. Also, the applicability of zero voltage switching at turn on, zero current transition at turn off has been verified experimentally. Computer simulations and experiment on a 50 Hz power supply show that the new controller is effective and easy to implement for modular multilevel inverters.